Gender resolution in Croatian, Slavic and Proto-Indo-European - Matasović, Ranko (Array, 2019)
This paper deals with the origin and development of the gender resolution rule according to which the predicate adjective agrees with the masculine antecedent when there is agreement with a conjunction of subjects at least one of which denotes a male person. Apart from Croatian, such a rule exists (or existed) in the other Slavic languages, as well as in Baltic languages, so it can safely be posited for Proto-Slavic and Proto-Balto-Slavic. We further show that most contemporary and ancient Indo-European languages had such a gender resolution rule. Where such a rule does not exist (as in Germanic languages), there is a plausible historical explanation. In Hittite, which preserves the most ancient gender system of Indo-European (with only common and neuter genders, and no feminine gender), the default agreement is with the common gender noun. Recent advances in our understanding of the development of gender in Indo-European allow us to show that the rule taking the masculine as the default gender has developed from the rule taking the common gender as default. This is because the morphemes showing gender agreement on adjectives and pronouns of the masculine gender have developed from Early Proto-Indo-European morphemes expressing the common gender.